Cognitive-emotional coping mechanisms accessed by students in the current pandemic context - Rus, Mihaela; Sandu, Mihaela Luminita; Dodu, Alisa Ancuta; Filipov, Adela Marinela (Technium Social Sciences Journal, 2022)
Since the onset of 2019, the new coronavirus (SARS-CoV-2) and its associated disease (COVID-19) have had and continue to have a considerable negative impact worldwide on physical and mental health, but also on daily activities. Various precautionary measures have been put in place to prevent the spread of the virus, measures that have significantly affected various areas and activities, including social, professional, educational, family, sports. Therefore, both the negative experience experienced with the advent of the virus and its rapid spread, as well as the limits imposed by the authorities, have determined a series of negative emotions among the entire population. One of the crucial aspects of everyday life is the management of emotions. The concept of coping or emotional regulation involves a series of processes that organize emotions, processes that can change, shape or inhibit a certain emotional state. Improper management of emotions can cause significant discomfort that persists over time and can cause a variety of symptoms (Gross, 2014 apud Cuevas Lopez et al., 2021). In the current pandemic context, in which negative experiences have increased due to infection with the new virus, but also because of the restrictions that have prevented the normal functioning of the entire population, improper management of emotions is not a topic that must be neglected. This paper starts from the ideas illustrated above and focuses its attention on the students, who have experienced considerable changes during this pandemic period. The main purpose of this paper is to understand the coping strategies adopted by students in the current pandemic context. In order to achieve our goal, in a first stage we will present the main defining aspects of the studied variables, namely emotions and emotional regulation strategies. The study investigates the following 9 coping strategies - self-curing, acceptance, rumination, positive refocusing, positive reassessment, putting into perspective, catastrophizing and blaming others. Another objective that the present research proposes is to highlight the extent to which the coping strategies adopted during the pandemic period differ in the students employed from the unemployed students, respecting the students from the Faculty of Psychology compared to the students from the Faculty of Law. Also, the study aims to bring a novelty to the researches, thus presenting the coping strategies adopted by the students of the Romanian population during this delicate period.